Methicillin-Resistant and Biofilm-Producing Staphylococcus aureus in Nasal Carriage among Health Care Workers and Medical Students. (4th January 2023) - Saud, Bhuvan; Khatri, Gita; Amatya, Neetu; Paudel, Govinda; Shrestha, Vikram
Abstract : Antimicrobial resistance (AMR) is a global threat. It has been portrayed as a slow tsunami. Multidrug resistance and extensive drug resistance exacerbate the already-existing AMR problem. The aim of the study was to access the colonization of methicillin-resistant and biofilm-producing Staphylococcus aureus among healthcare workers (HCWs) and medical students (MSs). A cross-sectional study was designed. A total of 352 participants (176 were HCWs and 176 were MSs) were enrolled from different hospitals and medical colleges in Kathmandu, Nepal. Nasal cavity swab samples were collected and inoculated on Mannitol salt agar at standard in-vitro environmental conditions. Isolates were identified based on colony characteristics, staining properties, and biochemical tests. Identified isolates were tested for antibiotic susceptibility and biofilm production. Out of 352 participants, 65.3% were S. aureus carriers; among the carriers, 52.2% were HCWs and 47.8% were MSs. Of the total isolates, 47.4% isolates were methicillin-resistant S. aureus (MRSA) and 73.9% isolates were multidrug-resistant (MDR). Among MDR isolates, out of 109 MRSA isolates, 86.2% were MDR and out of 121 MSSA isolates, 62.8% were MDR where isolates were mainly resistant to erythromycin. In addition, 68.7% isolates were biofilm-forming; the results were similar in both MRSA and MSSA. Variables such as profession and educational level showed statistical significance (p  < 0.05) with MRSA, MSSA, and biofilm producers. In conclusion, asymptomatic colonization of healthcare workers by drug-resistant S. aureus is increasing at alarming rates. This reflects the lack of proper hygiene practice as well as improper disinfection of workplace of study population.